2001
DOI: 10.1093/jn/131.3.740
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Bran and Soy Protein Feeding Do Not Alter Urinary Excretion of the Isoflavan Equol in Premenopausal Women

Abstract: The capacity to convert the soy isoflavone daidzein to equol in vivo is presumably determined by an individual's intestinal microfloral populations; however, diet may also influence this conversion. The objectives of the present study were to determine whether a 1-mo supplementation of dietary fiber as wheat bran increases urinary equol excretion in equol excreters and stimulates equol production in nonexcreters and whether longer-term soy isoflavone intake increases equol production or alters overall urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
59
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 23 publications
10
59
2
Order By: Relevance
“…Although equol excretion has been positively correlated with total fat and meat intake and fat-to-fiber ratio (Adlercreutz et al, 1991), processed and high-fat meat (Lampe et al, 1999) and carbohydrate, fiber, plant protein, and percent of energy as carbohydrate (Lampe et al, 1998;Rowland et al, 2000), our findings agree with other research showing no unique dietary patterns in equol excretors (Hutchins et al, 1995;Duncan et al, 2000;Lampe et al, 2001). Our results showing no differences in age, body weight, BMI, and cycle length between excretors and nonexcretors also agree with previously published results (Duncan et al, 2000;Lampe et al, 2001). However, these results must be interpreted with caution, as they are limited by small sample sizes, homogenous populations, and insensitive dietary assessment tools.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although equol excretion has been positively correlated with total fat and meat intake and fat-to-fiber ratio (Adlercreutz et al, 1991), processed and high-fat meat (Lampe et al, 1999) and carbohydrate, fiber, plant protein, and percent of energy as carbohydrate (Lampe et al, 1998;Rowland et al, 2000), our findings agree with other research showing no unique dietary patterns in equol excretors (Hutchins et al, 1995;Duncan et al, 2000;Lampe et al, 2001). Our results showing no differences in age, body weight, BMI, and cycle length between excretors and nonexcretors also agree with previously published results (Duncan et al, 2000;Lampe et al, 2001). However, these results must be interpreted with caution, as they are limited by small sample sizes, homogenous populations, and insensitive dietary assessment tools.…”
Section: Discussionsupporting
confidence: 91%
“…A more recent study using a soy or wheat-bran intervention was unable to alter excretion from baseline (Lampe et al, 2001). Probiotic consumption did not significantly reduce plasma reproductive hormones, although the bacteria provided were similar in dose and bacterial species to those previously shown to significantly lower fecal b-glucuronidase activity in humans (Goldin and Gorbach, 1984;Benno and Mitsuoka, 1992).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In the current study, 12 subjects (39%) consistently metabolized daidzein to equol, a similar proportion to that reported in other soy studies (52)(53)(54). All four soy dietary periods increased plasma equol levels in the initial (0 h) measurement, implying that 5 weeks of daily soy intake (with or without a probiotic or prebiotic) was sufficient to increase plasma equol in those who are predisposed to this conversion.…”
supporting
confidence: 87%
“…Conversely, isoflavone excretion after a soy-rich meal was reduced by 13% when accompanied by a wheat fibre supplement (Tew et al, 1996). However, two other studies found no changes in isoflavonoid excretion after treatment for 1 month with soy combined with a wheat fibre supplement (Lampe et al, 2001) or an increased intake of fat and protein . Discrepancies could arise from differences in design: two studies Rowland et al, 2000) focused on equol and did not evaluate total isoflavonoids, while in two other trials (Tew et al, 1996;Xu et al, 2000), the experimental period of 1day may have been inadequate and data on the isoflavonoid metabolites were not reported.…”
Section: Discussionmentioning
confidence: 96%